Impact of Front Line Demonstrations on Yield, Knowledge Adoption and Horizontal Spread of Clusterbean Crop in Hot Arid Zone: An Assessment - Singh, Bhagwan; Sharma, A K (Annals of Arid Zone, 2019)
The study was conducted in Bheenjwdia village of Jodhpur district of Rajasthan during 2010 to 2014 to assess the impact of Front Line Demonstrations (FLDs) of clusterbean crop in hot arid zone on the parameters like enhancement in yield, increase in knowledge, adoption of technology and extent of horizontal spread of clusterbean production through FLDs. The data were collected from 96 farmers and analyzed. The results of the study revealed that the yield of clusterbean crop under demonstration was 32.71% higher as compared to farmer’s practices. The overall knowledge and adoption level of production technology of clusterbean was increased by 44.82 and 224.45%, respectively due to front line demonstrations. The local variety of clusterbean was replaced by RMG-112, RGC-936, RGC-1003, HGS-365 in demonstration areas. This significantly increased horizontal spread by 486.04%. Key words: Front line demonstration, adoption, horizontal spread